Science: Maintaining the purity of the reading of the Qur'an - Nada Ramadhania; Mariza Laili; Muhammad Ade Rizky; Edi Hermanto (Yayasan Adra Karima Hubbi, 2024)
Background. Tahsin science is a branch of knowledge in Islamic studies which aims to maintain the purity and beauty of the reading of the Koran. In this context, tahsin comes from the Arabic word which means